LEGAL STUDY OF THE INKRACHT DECISION ON UNFAIR BUSINESS COMPETITION IN TRADEMARK DISPUTES (CASE STUDY OF THE LEAF TRADEMARK DISPUTE IN THE SEMARANG COMMERCIAL COURT OF CENTRAL JAVA AND THE NGANJUK DISTRICT COURT OF EAST JAVA) - Lisa Agustiana; Martin Roestamy; Jacobus Jopie Gillalo (Penelitian dan Pengembangan Ilmu, 2025)
This article critically examines the final and binding court decisions (inkracht) in the trademark dispute between Rudy Mulyanto and PT. Unichemcandi Indonesia over the “Daun” trademark. The research is motivated by the increasing number of trademark disputes in Indonesia, which often result in unfair business practices such as predatory pricing and misuse of legal mechanisms by registered trademark owners. The study employs a normative juridical approach supported by empirical data through court decisions, expert interviews, and legal literature. Findings indicate inconsistencies in law enforcement between the Commercial Court and the District Court rulings, as well as potential misuse of the judiciary to seize market share. The article highlights the urgency of consistency in law enforcement, strengthening the role of the Supreme Court in ensuring legal certainty, and harmonizing regulations to foster fair competition in the Indonesian market.